A study on assessment of HbA1c level as a diagnostic criterion of type 2 diabetes mellitus - Dutta, Agnibha; Dudhe, Ashish P; Deb, Subhasish; Dasgupta, Somnath; Sarkar, Amit (Asian Journal of Medical Sciences, 2015)
Aims and Objectives: We compared performance of HbA1c in diagnosis of type 2 diabetes mellitus with that of fasting plasma glucose and tried to determine cut off point of HbA1c for optimum sensitivity and specificity in a population of eastern India both from urban and rural background. Materials and Methods: The analysis was conducted in persons aged between 40 and 80 years, visiting our institution, who are newly diagnosed as diabetic and non-diabetic attending hospital for some other reason, who underwent FPG and HbA1c testing, in the time period January 2013 to August 2014. Results: From 100 individuals (mean age 54.6 years) HbA1c ? 6.5% produced sensitivity of 90% and specificity of 72%, positive predictive value 76.27% and negative predictive value 87.80% when compared to FPG ? 126 mg% as standard. By ROC curve, optimum cut off point for HbA1c was found to be 7.05% for diagnosis of diabetes. Conclusion: Using a cut off value of HbA1c of 7% may optimise detection of diabetes mellitus and ensure proper patient care. Asian Journal of Medical Sciences Vol.7(1) 2015 49-52